PENGARUH FDR DAN NPF TERHADAP RETURN ON ASSET (ROA) PADA BANK SYARIAH MANDIRI TAHUN 2009-2019 - Dezara Yogi Winata; Choiril Anam (Istithmar: Jurnal Studi Ekonomi Syariah, 2020)
This research is conducted with the aim to determine the effect of Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) on Return On Assets (ROA) at Bank Syariah Mandiri in 2009-2019. This research is a quantitative study with secondary data based on time series data. The data were processed using the IBM SPSS 25 program. The results showed that the FDR variable did not have a significant effect on Return On Assets (ROA). This is evidenced by the results of the tcount of 0.164 and ttable of 1.683 or tcount <ttable which means that H0 is accepted and H1 is rejected. The NPF variable has a negative and significant effect on Return On Assets (ROA). This is evidenced by the results of tcount of -4.841 and ttable of 1.683 or tcount> ttable which means that H0 is rejected and H2 is accepted. FDR and NPF variables have a significant effect on Return On Assets (ROA). This is evidenced by the value of Fcount of 11.745 and Ftable of 3.23 or Fcount> Ftable which means that H0 is rejected and H3 is accepted. Based on the results of the coefficient of determination, it can be seen that the FDR and NPF have an effect of 36.4% on Return On Assets (ROA). While the remaining 63.6% is influenced by other factors outside of the research.